(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
It is weII known that Iraq was alerted to the fact the need to catch up with globalization and the need to attract foreign investment , perhaps the solutions is able to or control over its economic problems which centers on the problem pf unemployment . Imposing the Investment Law No (13) for the year 2006 is the most basic steps to attract foreign investment through Madmen Law of incentives KaIiafaouat tax , it must be the study of those exemptions and compare them with tax exemptions for some of the investment Laws of the Arab countries as one investment Lebanese , Jordanian and Egyptian that we have the knowledge Marvel Law Iraqi investment in respect of such exemptions , as weII as know the role of these exemptions to encourage foreign investment in Iraq